AB0971 Characterisation of the patients at the time of the transition into the adult rheumatology. 63% of the patients are in remission at the time of the transition. (15th June 2017) - Tatsis, S; Foeldvari, I
Abstract : Background: The issue of transition from pediatric to adult rheumatology service is an emerging important topic. In 2012 a transition clinic was established according to the "Berliner Transitionsprogramm" [1] in cooperation of the Hamburger Zentrum für Kinder-und Jugendrheumatologie and the Rheumatology Unit of the Marien Hospital in Hamburg. The Berliner programm suggests three visits of the patient in transitionprocess, in the presence of the pedriatic and an adult rheumatologist together, and the fourth visit conducted by the adult rheumatologist alone. We present the characteristics of the patients at the time of the 4th visit. Objectives: To characterize the patient population at the time of enrollment into the adult service in the frame of our transition programm. Methods: We collected patient data starting 8/2012 to 11/2016. We summarized the patient population, who succesfully transitioned from pediatric to adult rheumatologic service, concerning diagnosis, sex, age at the time of diagnosis, disease duration at the time of transition, JADAS, HAQ, VAS globular assessment, VAS pain, medication and disease activity. Results: 73 patients were transitioned. 65% of them female. Mean age at diagnosis of the patients was 12.5 years. Mean disease duration at time of transition ws 10.8 years. The mean JADAS Score was 3.18 and the mean HAQ Score was 0.136. The patients global activity score was, on a VAS of 0 to 100, 14.03 and the global pain score, on a VAS of 0 to 100, 12.33. 39.7% of the patients received synthetic DMARDS and 34% biologic DMARDS: Only 1 patient received steroids. 24.6% of the patients were off medication. 63% of the patients were in remission, 61% of them on medication and 39% off medication in remission. Conclusions: In this monocenter cohort 63% of patients were in remission, and with the mean JADAS Score of 3.18 most of them have low disease activity under the current treatment. The mean HAQ Score with 0.136 reflects a score, which is expected in healthy controls. But 75.4% of the patients needed medication to achieve this good condition. The amount of patients on medication emphasize the need of the structured transition. References: Minden K, Niewerth M, Muther S: [Berlin transition program: from adolescents to adults in rheumatology treatment]. Z Rheumatol 2014, 73(6):526–531. Disclosure of Interest: None declared